REDESIGN VISUAL IDENTITY PONDOK SEPATU SAMILLO PADANG - NADIA ULJANNAH, Drs. Nasrul Kamal, M.Sn., Dini Faisal, M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
The Pondok Sepatu Samillo a local industry engaged in the production of sandals and shoes. Businesses that took place in the Veteran No. 3 Padang, is a family business passed down from generation to generation. Pondok Sepatu Samillo as well as other businesses, are still concerned with the benefits funsional course, has not been able to provide emotional benefits.It can be seen from different angles, ranging from the logo used not reflect the identity of Pondok Shoes Samillo, still have a lot in common with a similar business in the city of Padang. Not having a differentiator with other competing products. Products packaged or displayed sober, having no identity that can be recognized properly. Thus the visual identity Samillo cottage Shoes are not currently able to display the identity of the business, so do not have emotional value and yet provide emotional benefits for consumers. That requires Redesign Visual Identity Pondok Sepatu Samillo Padang.The analytical method used in the redesigned visual identity Pondok Sepatu Samillo, using SWOT analysis (Strength, Weakness, Opportunity, Threat). This design includes designing a logo that identifies Pondok Sepatu Samillo and their application to identity guidelines, signage, stationary sets such as labels, business cards, letterheads, envelopes, notes, note pad, uniform, apron, post-it and stamp. As well as product packaging such as shoe boxes and shopping bags. Hopefully, by the redesigned visual identity Pondok Sepatu Samillo, it can provide the identity of the business, which could give the distinguishing characteristics or other business. So the visual identity of Pondok Sepatu Samillo can give emotional valueKeywords: Visual Identity, Pondok Sepatu Samillo, Emotional Value